2021
DOI: 10.1186/s13054-021-03858-1
|View full text |Cite
|
Sign up to set email alerts
|

Persisting neuroendocrine abnormalities and their association with physical impairment 5 years after critical illness

Abstract: Background Critical illness is hallmarked by neuroendocrine alterations throughout ICU stay. We investigated whether the neuroendocrine axes recover after ICU discharge and whether any residual abnormalities associate with physical functional impairments assessed 5 years after critical illness. Methods In this preplanned secondary analysis of the EPaNIC randomized controlled trial, we compared serum concentrations of hormones and binding proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Additionally, neuroendocrine alterations in patients with sustained muscle weakness are associated with decreased physical recovery. A higher reverse T3, and lower T3-reverse T3 ratio was found to be associated with lower HGS and shorter 6MWD five years after critical illness [ 32 ▪ ]. Persisting abnormalities within the thyroid axis may increase the risk of long-term physical impairment.…”
Section: Pathogenesismentioning
confidence: 99%
“…Additionally, neuroendocrine alterations in patients with sustained muscle weakness are associated with decreased physical recovery. A higher reverse T3, and lower T3-reverse T3 ratio was found to be associated with lower HGS and shorter 6MWD five years after critical illness [ 32 ▪ ]. Persisting abnormalities within the thyroid axis may increase the risk of long-term physical impairment.…”
Section: Pathogenesismentioning
confidence: 99%
“…In this regard, a recent study found normalized ACTH and cortisol concentrations 5 years after critical illness. 41 However, this study included both short- and long-stay critically ill patients and may be confounded by survivor bias.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of suspicion of CIRCI and GC treatment, mainly with hydrocortisone, endocrinological follow-up is suggested for the patient. On the other hand, two studies have demonstrated that CIRCI is likely a reversible condition [28,29]. In our experience, adequate follow-up of patients who developed central adrenal insufficiency, even in a mild form, after GC treatment is essential in order to better evaluate HPA axis integrity without interfering conditions related to concomitant drugs or even hospitalization-induced stress.…”
Section: Conflict Of Interestmentioning
confidence: 91%